Trust and Trustworthy Computing 4th International Conference, TRUST 2011, Pittsburgh, PA, USA, June 22-24, 2011. Proceedings - McCune, Jonathan M.; Balacheff, Boris; Perrig, Adrian; Sadeghi, Ahmad-Reza.; Sasse, Angela; Beres, Yolanta; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Trust and Trustworthy Computing, TRUST 2011, held in Pittsburgh, PA, USA in June 2011. The 23 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers are organized in technical sessions on cloud and virtualization, physically unclonable functions, mobile device security, socio-economic aspects of trust, hardware trust, access control, privacy, trust aspects of routing, and cryptophysical protocols.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Computers and Society; Information Systems Applications (incl.Internet).